Towards Sustainable Solutions: Advancing ESG metrics in the Renewable Energy Sector - Vergara Arenas, Izabella; Molina Trujillo, Daniela; Rojas, Carola (Latin American Journal of Trade Policy, 2024)
The renewable energy sector is experiencing a seismic demand as stakeholders, sovereign wealth funds, and governments intensify pressure for transition from traditional fuel sources. Companies traditionally focused on fossil fuels are diversifying into renewables, drawn by decreasing costs and advancing technologies. However, the rapid expansion of renewable energy projects brings its own set of risks, tied to large-scale infrastructure and evolving regulatory landscapes. As the sector grows, disputes loom on the horizon. Stakeholders’ ability to anticipate and manage these disputes becomes paramount for effective transition and risk mitigation. Disputes in renewable energy projects could impact different parties and stakeholders of a company’s supply chain process. Notably, the critical and growing impact of climate change and the increasing influence of Environmental, Social, and Governance (ESG) standards set renewable energy projects apart from others. In this context, question if the existing dispute resolution mechanisms are tailored to renewable energy’s unique challenges is essential. Specialized courts or tribunals well-versed in renewable energy law and dispute resolution can enhance these mechanisms, especially arbitration and mediation procedures. This paper argues that implementing these changes in the existing dispute resolution mechanisms ensures fairness, equity, and success in renewable energy projects, aligning them with the global mission to combat climate change. As Africa and Latin America are seen as key for the development of energy transition, all dispute resolution developments should be especially sensitive to these region’s particularities to effectively meet sustainable solutions. Promoting a setting where disputes are efficiently resolved could contribute positively to the environmental crisis.